MUSEUM-BASED RECREATIONAL LEARNING: EXPLORING HISTORY AT THE NORTH SUMATRA PROVINCIAL STATE MUSEUM - Andi Zulkifli Tirta Andi (NAPAK TILAS: Jurnal Pendidikan Sejarah dan Ilmu Sejarah, 2026)
Museums have increasingly become important educational institutions that provide opportunities for experiential, interactive, and recreational learning. Unlike conventional classroom-based instruction, museum-based learning allows students to engage directly with historical artifacts, cultural objects, and tangible evidence of the past. This study explores the role of the North Sumatra Provincial State Museum as a medium for recreational history learning. The museum serves not only as a repository of cultural heritage but also as an educational environment that promotes historical understanding through enjoyable and meaningful experiences. This article employs a qualitative descriptive approach based on literature review, observation reports, and previous studies concerning museum education and the North Sumatra Provincial State Museum. The findings indicate that museum-based recreational learning enhances students’ historical awareness, cultural appreciation, critical thinking skills, and motivation to learn history. Through direct interaction with collections representing the diverse ethnic groups of North Sumatra, learners gain authentic experiences that cannot be obtained solely through textbooks. The museum’s collections, exhibitions, and educational programs contribute significantly to creating engaging learning experiences while preserving local cultural heritage. The study concludes that the North Sumatra Provincial State Museum functions as an effective learning resource that combines education and recreation, making history learning more meaningful and enjoyable for students.